(3GdPNjQIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3cfGT KGHJ Hf bQI GdeSei GdPNjQI , hgh jTJed Ydi eG jMJGL Gdjg ai Yde GdWH ai hUa GdOGA hGdOhGA s
(3JfJgi YfO GdebGdI GdSGOSI hGdYTQjfs
(3bWYI ef fSNI CNQi JHOC HChd GdcJGH hChdgG agQS ddebGdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B89 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs